Influence of Acceleration Field Curvature on Physical and Numerical Modeling of Liquefiable Slopes in Geotechnical Centrifuge Tests - Mohamed A. ElGhoraiby; Majid T. Manzari (Geotechnics, 2025)
Geotechnical centrifuge modeling is a powerful tool for investigating the behavior of geo-structural systems under realistic stress conditions. To accurately replicate the radial nature of the centrifugal acceleration field, the model surface is often curved—a detail that can significantly influence soil response. This study explores the effectiveness and limitations of incorporating surface curvature in centrifuge models through a series of nonlinear finite element analyses, utilizing an advanced constitutive model for liquefiable soils. Focusing on mildly sloping ground, the numerical models are carefully calibrated and verified for convergence to ensure accurate simulation of soil cyclic behavior. The analysis reveals that neglecting surface curvature can lead to artificially dilative responses and underestimation of liquefaction-induced lateral spreading. By modeling several centrifuge experiments under varied scaling conditions, we demonstrate that including surface curvature yields pore pressure and deformation patterns more consistent with full-scale, gravity-driven responses. These findings underscore the critical role of geometric accuracy in both physical and numerical centrifuge modeling of seismic soil behavior.